2022
DOI: 10.1002/ehf2.14222
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profiling to predict prognosis in patients with heart failure: an expert review

Abstract: Heart failure is a complex disease with a poor prognosis. A number of widely used prognostic tools have limitations, so efforts to identify novel predictive markers and measures are important. As a metabolomics tool, amino acid profiling has shown promise in predicting heart failure prognosis; however, the evidence has not yet been sufficiently evaluated. We describe the utilization of amino acids in the healthy heart and in heart failure before reviewing the literature on amino acid profiling for prognostic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The median (interquartile range) MAGGIC score was 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), NT-proBNP (N-terminal pro-B-type natriuretic peptide) level was 8899 (4184-16351) pg/mL, and 43% of the patients had an EF <50%. Most patients were hypertensive and more than a third were diagnosed with diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (interquartile range) MAGGIC score was 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), NT-proBNP (N-terminal pro-B-type natriuretic peptide) level was 8899 (4184-16351) pg/mL, and 43% of the patients had an EF <50%. Most patients were hypertensive and more than a third were diagnosed with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 We also found BCAAs (valine, leucine, and isoleucine) provided a protective contribution to our MRS. BCAAs are essential amino acids associated with protein metabolism in the heart and skeletal muscles, which have been studied in muscle wasting disorders. 21,22 Previous studies using different panels of metabolites similarly identified BCAAs as key risk indicators, 6 leading to hypothesize that these associations could reflect the systemic skeletal muscle response in advanced HF states. Our group previously reported on an association between the Metabolic Malnutrition Index, which includes BCAAs, and an increased risk of mortality in this HF community cohort.…”
Section: Specific Metabolites and Biological Plausibilitymentioning
confidence: 99%
“…Cellular catabolism of BCAA includes deamination to yield branched-chain alpha-keto acids (BCKA), which undergo conversion mediated by BCKA dehydrogenase to the precursors of energy metabolism molecules such as acetyl-CoA and succinyl-CoA. While BCKA dehydrogenase kinase phosphorylates BCKA dehydrogenase and inactivates the enzyme, dephosphorylation by a specific phosphatase restores the enzyme activity [ 23 , 24 ]. Endotoxins and inflammatory cytokines, whose levels are increased in HF, are strong inducers of BCKA dehydrogenase activity in the skeletal muscle [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,14 In fact, a wide range of AAs are produced from protein metabolism and tissue degradation, and these AAs can be measured to inform the state of metabolism in HF and adverse events. 15,16 Nevertheless, little is known about the association between the ratio of tyrosine (Tyr) to threonine (Thr) and HF disease, especially with different HF aetiology. The purpose of our study was to examine the relationship between Tyr/Thr ratio and stable chronic HF (HFrEF or HFmrEF), meanwhile, comparing it with the FR index for better managing HF disease in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a wide range of AAs are produced from protein metabolism and tissue degradation, and these AAs can be measured to inform the state of metabolism in HF and adverse events 15,16 . Nevertheless, little is known about the association between the ratio of tyrosine (Tyr) to threonine (Thr) and HF disease, especially with different HF aetiology.…”
Section: Introductionmentioning
confidence: 99%